Síntese, caracterização e avaliação catalítica, em reação foto-Fenton, de compósitos Fe2O3/grafite - Grassi, Patrícia (2018)
The presence of dyes in wastewater, most of them recalcitrant, contaminate the aquatic environment, as they prevent the penetration of light, damaging the local fauna and flora. In addition, they may cause carcinogenic and genotoxic effects to animals and human health. Therefore, it is important to remove these contaminants from wastewater. This work evaluated the efficacy of Fe2O3 / Grafite catalysts in the degradation of amaranth red dye in photo-Fenton reaction under visible light. The deposition of iron oxide nano particles on the graphite was performed using the impregnation technique, using different iron concentrations (1-15%). Composites named G1, G2.5, G5, G10 and G15 were synthesized, where the numerical values corresponded to Fe2O3 (% by weight) impregnated with graphite. By means of X-ray diffraction (XRD) analysis, graphite (G) showed a characteristic peak (26.4 °) and that the incorporation of Fe2O3 led to a reduction in the intensity of graphite diffraction peaks. In addition, the increase in iron content resulted in the approximately 10-fold increase in the specific surface area at G15 relative to the unsupported graphite (G). Through the analysis of scanning electron micrographs (SEM) of the catalysts obtained, it can be seen that the iron oxide is deposited on the surface of the graphite, in the form of agglomerates of small particles. Degradation efficiencies of the catalysts G, G1, G2.5, G5, G10 and G15 were 2, 12, 32, 44, 76 and 80%, respectively. In addition, raising the Fe2O3 content from 10% (G10 sample) to 15% (G15 sample) did not provide substantial gain in activity. This behavior may be due to the formation of Fe2O3 particle agglomerates on the graphite surface when higher contents are deposited. As result, the use of the G10 catalyst in the determination of the best operating conditions in the photo-Fenton system was chosen using the Rotational Central Compound Design. The optimum conditions of photo-Fenton reaction for the removal of amaranth red dye were: pH 2.5, amount of catalyst 0.35 gL-1 and molar ratio H2O2 / Σmineralizable: 4.7, promoting removal of 93% of the color of the solution in 30 minutes of reaction.